2022
DOI: 10.1186/s12937-022-00790-0
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting two days versus one day per week, matched for total energy intake and expenditure, increases weight loss in overweight/obese men and women

Abstract: Background Intermittent fasting (IF), consisting of either a one-day (IF1) or two consecutive days (IF2) per week, is commonly used for optimal body weight loss. Our laboratory has previously shown an IF1 diet combined with 6d/week of protein pacing (P; 4–5 meals/day evenly spaced, ~ 30% protein/day) significantly enhances weight loss, body composition, and cardiometabolic health in obese men and women. Whether an IF1-P or IF2-P, matched for weekly energy intake (EI) and expenditure (EE), is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 55 publications
3
18
1
Order By: Relevance
“…Moreover, dietary fiber intake significantly increased (8-12 g/d), whereas sugar (-57 to 77 g/d) and sodium (-1,500 to 2,000 mg/d) significantly decreased. As previously reported, both groups maintained similar physical activity and energy expenditure throughout the weight loss period (31).…”
Section: Participant Characteristicssupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, dietary fiber intake significantly increased (8-12 g/d), whereas sugar (-57 to 77 g/d) and sodium (-1,500 to 2,000 mg/d) significantly decreased. As previously reported, both groups maintained similar physical activity and energy expenditure throughout the weight loss period (31).…”
Section: Participant Characteristicssupporting
confidence: 85%
“…Reductions have been observed in other short-term weight loss trials with suggestive susceptibility to food cravings (92). In contrast, these behaviors were not reflected in participants from the present study as hunger ratings significantly improved over baseline levels (31). The other notable negative correlation was fatty acid biosynthesis.…”
Section: Discussioncontrasting
confidence: 57%
“…In a study of healthy adults with overweight and obesity using meal replacements on fasting days, short-term fasting (4 weeks) resulted in greater weight loss and improved body composition and cardiometabolic health without exacerbating the feeling of hunger or adversely affecting appetite. 47 The investigators also found that two days of fasting per week was more beneficial than one day. Higher protein intake and more frequent eating were shown to reduce the amount of total and abdominal fat and improved LBM and postprandial thermogenesis; both were effective for long-term weight maintenance and are feasible for patients with overweight or obesity.…”
Section: If Combined With Other Interventionsmentioning
confidence: 99%
“… 60 Short-term (4 weeks) IF decreased body weight and improved body composition and cardiometabolic health while having no adverse effects on the feeling of hunger or appetite, whereas long-term (52 weeks) IF reduced the amount of total and abdominal fat and increased LBM, thereby promoting weight maintenance. 47 , 49 A lower LBM is associated with a lower metabolic rate and neuromuscular function, fatigue, and increased risk of injury, with the degree of LBM reduction positively correlated with weight regain. 61 Thus, a reasonable weight loss goal is to reduce body fat while avoiding loss of muscle mass.…”
Section: Evaluation Of the Effect Of Ifmentioning
confidence: 99%
See 1 more Smart Citation